A comparative analysis of the Employment Tax Incentive Act, no.26 of 2013 - Odendaal, Petrus Johannes Loock (Department of Finance and Tax, 2016)
Despite being internationally recognised as an economic powerhouse of the African continent, South Africa struggles to overcome certain socio-economic problems, which predominantly stem from the inequalities within its society. One of the most important areas of prevailing concern is high unemployment, particularly amongst the youth segment of the population. Approximately 42% of South Africans under the age of 30 are unemployed, a fate shared by less than 17% of those above 30 years of age. The South African government appropriately sought to ensure a better future for all its citizens by 'creating', or facilitating the creation, of more jobs. As part of its 'program of action', one of the initial steps was to enact the Employment Tax Incentive Act, No. 26 of 2013 ('ETIA'). The following extract is from the Explanatory Memorandum on the Employment Tax Incentive Bill, 2013: "High youth unemployment means young people are not gaining the skills or experience needed to drive the economy forward. (…) In response to the high rate of youth unemployment, government wishes to implement an incentive mainly aimed at encouraging employers to hire young and less experienced work seekers, as stated in the National Development Plan. The incentive is one among many that will fall under the umbrella of government's youth employment strategy, the National Youth Accord, which outlines a program of action to address youth unemployment." The primary aim of this study is to conduct a detailed analysis of the ETIA in order to ultimately evaluate its merits, i.e. by expressing an opinion on whether or not it is assisting in combatting youth unemployment. The analysis compares similar types of legislation that have been implemented, both successfully and unsuccessfully, in other countries in attempts to address similar unemployment issues. This paper reflects events, legislation and published literature as at 1 December 2015.